Determinan Kinerja UMKM: Fintech Lending, Modal Usaha dan Orientasi Pasar - Agnes Febriyani; Maria Rio Rita (Postgraduate Program Merdeka University, 2022)
The purpose of this research is to analyze the effect of fintech lending, venture capital, market orientation on MSME performance. In business performance, MSME owners still have problems using fintech lending, limited capital and market orientation knowledge. However, the existence of fintech lending can facilitate sales transactions and can provide capital easily. There are 250 SMEs registered in Kupang Village, then through the sample collection method using purposive sampling and obtained 50 manufacturing SMEs. The analytical technique used in this research is multiple linear regression. The results of this study indicate that business capital and market orientation have a positive influence on the performance of MSMEs. Fintech lending has no effect on the performance of MSMEs.DOI: https://doi.org/10.26905/afr.v5i2.7761